New Zealand : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2001 Article IV Consultation highlights that since early 2001, domestic demand growth has recovered in New Zealand and contributed to sustain GDP growth in the wake of weaker net exports, owing to the economic slowdown in the rest of the world. The sharp rise in economic activity pushed the economy to a high level of resource use, as capacity utilization rates rose markedly in 2001. An improvement in business and consumer confidence in the first months of 2002 suggests that domestic demand is likely to maintain its momentum in the first half of 2002.